PERBANDINGAN EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING, PROJECT BASED LEARNING, DAN PEMBELAJARAN KONVENSIONAL TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA - Karlena, Eenti; Hilyati Milla; Merri Sri Hartati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the differences in learning motivation and student learning outcomes through the application of Problem Based Learning (PBL), Project Based Learning (PjBL), and conventional learning models in Social Studies subjects. This study uses a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The study was conducted at SMPN 8 Bengkulu Tengah with a population of 83 seventh-grade students determined using a total sampling technique. Data were collected through learning outcome tests, learning motivation questionnaires, and observations. Data analysis was carried out using normality tests, homogeneity tests, One Way ANOVA, and Post Hoc follow-up tests. The results showed that there were significant differences in learning outcomes between the PBL, PjBL, and conventional learning groups based on the ANOVA test (Sig. = 0.000). The highest increase in learning outcomes descriptively was in the PBL group, followed by the PjBL and conventional learning groups. However, the results of the Post Hoc test showed that there was no significant difference between the PBL and PjBL groups (Sig. = 0.537), so that both models had relatively the same effectiveness in improving student learning outcomes. Furthermore, the implementation of active learning demonstrated better learning motivation compared to conventional learning. These findings suggest that PBL and PjBL can be effective alternative social studies learning strategies for improving student motivation and learning outcomes through active and contextual learning.